PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMPN 40 PADANG - Saputra, Andika (Departemen Matematika, 2023)
Mathematic has a main goals for students to have problem-solving abilities. However, students’ mathematical problem-solving skills are still low due to teacher-centered learning approaches. The proposed solution is to implement Two Stay Two Stray (TSTS) instructional model, and therefore this study is aimed to figure out the impact on mathematical problem-solving abilities by using TSTS instructional model. Quasy Experiment is the research method that employed with a design known as the Nonequivalent Posttest Only Control Group Design. All 8th-grade students at SMP Negeri 40 Padang during the 2022/2023 academic year is the population, and there were two samples. This study using an instrument which is a final test. Using the outcomes of the hypothesis test from the conclusive examination acquired a P-value was 0.000 (0,05), which indicates rejecting the null hypothesis (. It was discovered that there is an impact on students' mathematical problem-solving abilities in class VIII at SMP Negeri 40 Padang by using the TSTS instructional model.Keywords– Problem-solving abilities, creative problem solving learning model, direct instructional model